Вы находитесь на странице: 1из 9

.

1) .
sin x = 1

x =

+ 2n, n
2

1
x = + 2 n, n
2

1
2 + 2n 0, n

2
1

x = + 2n , n
2

f ( x) = g ( x)

1
n 4 ,n

2
1

x = + 2n , n
2

g ( x) 0

f ( x) = g 2 ( x)
2

: x = + 2n , n
1
2

2) .
1
1 = ctgx cos x; x n, n
sin x
1 sin x cos x cos x sin x
=
sin x
sin x
1 x ( x 5) = 0

1 sin x = cos x(1 sin x )

x = 1 x = 5

x= 5

1 x 0

1 sin x cos x (1 sin x ) = 0

(1 sin x )(1 cos x ) = 0


sin x = 1

x = + 2k , k
2

cos x = 1

x = 2l , l

.
:

x = + 2m, m
2

: x =

+ 2m, m
2

3) .
3
sin 4 x + cos 4 x 2 sin 2 x + sin 2 2 x = 0
4

1
3
1 sin 2 2 x 2 sin 2 x + sin 2 2 x = 0
2
4
4 2 sin 2 2 x 8 sin 2 x + 3 sin 2 2 x = 0
sin 2 2 x 8 sin 2 x + 4 = 0
2

b
D1 = ac
a

sin 2 x = y ,
y 2 8y + 4 = 0

D1 = 12

x1, 2 =

b
D1
2
a

y1, 2 = 4 2 3
sin 2 x = 4 2 3

sin 2 x = 4 + 2 3

2 x = ( 1) arcsin 4 2 3 + k , k

..

x=

x R , .

1
( 1) k arcsin 4 2 3 + k , k
2
2
1
k
k
: x = ( 1) arcsin 4 2 3 + , k
2
2

sin 2 x 1

4)

.
sin x 2 = sin ( x 2 + 2 x ), x R
sin x 2 sin ( x 2 + 2 x ) = 0, x R
2 sin ( x ) cos ( x 2 + x ) = 0, x R
2 sin ( x ) = 0
cos ( x 2 + x ) = 0

( x 2 + x) =

x = n, n

+ k , k
2

1
+ k, k
2
1

x 2 + x + k = 0, k
2

D = 3 + 4k 0
3
k = 0,1,2,3....
k
4

x = n, n

x2 + x =

x1, 2 =

1 3 + 4k k = 0,1,2,3....
,
2

1 3 + 4k k = 0,1,2,3....
: x = n, n ; x1, 2 =
,
2

5)
.
tg ( x 15 0 )ctg (1 + 15 0 ) =

1
3

) .
0

cos x 15 0

sin x + 150 0

x 150 900 + 1800 k , k


0
x + 15 1800 n, n
x 150 + 900 + 1800 k , k

x 150 + 1800 n, n
:
x 15 0 + 90 0 +180 0 k , k
x 15 0 +180 0 n, n

) .
sin ( x 15 0 ) cos( x + 15 0 ) 1
=
sin ( x + 15 0 ) cos( x 15 0 ) 3

sin ( 30 0 ) + sin 2 x 1
=
3
sin 30 0 + sin 2 x
1
sin 2 x
2 =1
1 3
sin 2 x +
2

2 sin 2 x 1 1
=
2 sin 2 x + 1 3
sin 2 x 3 2 sin 2 x 1
=0
6 sin 2 x + 3

sin 2 x = 1

sin
2
x
=

2
sin 2 x = 1

sin
2
x

2
2 x = 90 0 + 360 0 m, m
x = 45 0 +180 0 m, m
: x = 45 0 +180 0 m, m

6) .
1
sin 4 x + cos 4 x = sin 2 x , x R
2
2

1
1 coc 2 x
1 + cos 2 x

+
= sin 2 x
2
2
2

1 2 cos 2 x + cos 2 2 x + 1 + 2 cos 2 2 x + cos 2 2 x = sin 2 x

2 + 2 cos 2 2 x = 4 sin 2 x 2
sin 2 2 x + 2 sin 2 x 3 = 0

sin 2 x = y ,
y2 + 2y 3 = 0

sin 4 x = sin 2 x

1
2

1
1 cos 2 x
2
=
= 1 sin 2 x
2
2

y1 = 1
y 2 = 3
sin 2 x = 1

2 x = + 2k , k
2

x = + k , k
4

: x = + k , k
4

sin 2 x = 3

..

sin 2 x 1

x R , .

7) .
,
.
a 0 sin n x + a1 sin n 1 x cos x + a 2 sin n 2 x cos 2 x + ... + a n 1 sin x cos n 1 x + a n cos n x = 0 ,
a0 ; a1 ; a 2 ;...; a n - . n - .
3 sin x + 4 cos x = 5, x

x
x
+ 4 cos 2 = 5 *1
2
2
x
x
x
x
x
x
6 sin cos + 4 cos 2 4 sin 2 = 5 sin 2 + 5 cos 2
2
2
2
2
2
2
x
x
x
x
9 sin 2 6 sin cos + cos 2 = 0
2
2
2
2
x
x
cos = 0 , sin = 0 ,
2
2
x
2 x
0 ,
, cos 0 . cos
2
2
x
x
9tg 2 6tg +1 = 0
2
2
3 sin 2

3tg 1 = 0
2

tg

x 1
=
2 3

x
1
= arctg + n, n
2
3
1
x = 2arctg + 2n, n
3
1
: x = 2arctg + 2n, n
3

8)
.
3 sin x + 4 cos x = 5, x

. . 32 + 4 2 5 2 , .
3 2 + 4 2 = 5 ,
3
4
sin x + cos x = 1
5
5

. .

3
4
1,
1
5
5

3 4
+ = 1 ,
5 5

cos sin x +sin cos x =1


sin ( x +) =1

, cos = 3 , sin = 4
5


+ 2k , k
2

x = + + 2k , k
2
4
x = arcsin + + 2k , k
5 2
x + =

4
5

: x = arcsin +

+ 2k , k
2

a cos x + b sin x = c
1) c = 0 , .
2) c 0 a 2 + b 2 0 (


a
a +b
2

cos x +

a +b
2

. .

a 2 +b 2

b 0),

,
c

sin x =
b

1;

a 2 +b 2

a +b
2

a + b2
2

2
2
a +b


b
+

2
2
a +b

= 1,

= cos ,
a + b2
c
sin cos x + cos sin x =
2
a + b2
c
sin ( x + ) =
2
a + b2

a +b
2

) ,

= sin ;

c
a +b 2

) ,

c
a +b 2
2

>1

. . a 2 + b 2 < c 2 , .

. . a 2 + b 2 c 2 ,
c

x + = ( 1) arcsin
k

x = arcsin

a + b2
2

a
a +b
2

+ k , k

+ ( 1) arcsin

3 sin x + 4 cos x = 6, x

+ k , k

a + b2
2

. . 3 2 + 4 2 < 6 2 , .
9)

.
x
2tg
2
sin x =
x
1 + tg 2
2

x
2
cos x =
x
1 + tg 2
2
x
2tg
2
tgx =
x
1 tg 2
2

3 sin x + 4 cos x = 5, x

(1)

x
2tg
1 tg 2
2
3
+4
2 x
1 + tg
1 + tg 2
2

(2)

x
2 =5
x
2

1 tg 2

6tg

x
x
x
+ 4 4tg 2 5 5tg 2
2
2
2 =0
x
1 + tg 2
2

x
2x
9
tg

6
tg
+ 1= 0
2
2

1 + tg 2 x 0

2
2

3tg 1 = 0
2

tg

x 1
=
2 3

x
1
= arctg + n, n
2
3
1
x = 2arctg + 2n, n
3

(1) (2), ,
, cos
cos

x
= 0 .
2

x
=0
2

x
= + n, n
2 2
x = + 2n, n

.
x = + 2n, n ,

3 sin ( + 2n ) + 4 cos( + 2n ) = 5, x
0 + 4( 1) = 5 - , x = + 2n, n , .

1
3

: x = 2arctg + 2n, n
10) .
( sin x cos x; sin x cos x ) = 0 sin x cos x = y ,
( sin x cos x ) 2 = y 2 , 1 2 sin x cos x = y 2 , 2 sin x cos x = y 2 1
2( sin x + cos x ) + sin 2 x +1 = 0, x R

2( sin x + cos x ) + 2 sin x cos x +1 = 0


sin x +cos x = y , ( sin x + cos x ) 2 = y 2 , 1 + 2 sin x cos x = y 2 , 2 sin x cos x = y 2 1 ,
y 2 + 2 y 1 + 1 = 0
y2 +2y = 0
y ( y + 2) = 0
y =0
y = 2

sin x + cos x = 0

cos x 0 ,
tgx = 1

sin x + cos x = 2 (3)

2 sin x + = 2
4

sin x + =
4
2

x =

. . sin x +

+ k , k

: x =

1 , x R , .
4

+ k , k

sin x cos x 2

, x R

sin x cos x = 2 sin x +


4

(3).
1. sin x + cos x .
2. tg
3.
4.
5.
6.

x
.
2

.
.
sin x cos x 2 , x R .
.

2( sin x + cos x ) + sin 2 x +1 = 0, x R

II

2( sin x + cos x ) + 2 sin x cos x + sin 2 x + cos 2 x = 0

2( sin x + cos x ) + ( sin x + cos x ) = 0


( sin x + cos x )( 2 + sin x + cos x ) = 0
2

sin x + cos x = 0

sin x + cos x = 2

2 sin x + = 2
4

sin x + =
4
2

cos x 0 ,
tgx = 1

x =

+ k , k

: x =

. . sin x +

1 , x R , .
4

+ k , k

11)
( ).
12)
.
1

1 cos x = sin x

sin x 0
(1)

2 ( 2)
1

cos
x
=
sin
x

2.
1 cos x = sin 2 x
cos 2 x cos x = 0

cos x( cos x 1) = 0

cos x = 0

cos x = 1


+ k , k
x2 = 2n, n
2
1 .

: x1 = + k , k , x2 = 2n, n
2
x1 =

2
sin x + 4 2 cos x = 0
sin x = 4 2 cos x

cos x 0
(1)

2 ( 2)
sin x = 2 cos x
2.

sin x = 2 1 sin 2 x

2 sin x + sin x 2 = 0
2

sinx .
sin x =

2
2

sin x = 2 , < 1,

1 .

: x =

3
+ 2n , n
2

Оценить